PENERAPAN BROW LAMINATION PADA ALIS TEBAL DALAM RIAS WAJAH PENGANTIN - Pambudi, Ika Prasetyani (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2023)
Ever-changing beauty trends always present a variety of new products and treatment methods, including brow lamination. Unlike eyebrow embroidery, brow lamination is claimed to have more natural and longer lasting results. Therefore, the aim of this research is to analyze the application of laminating thick eyebrows to bridal makeup. This research uses a qualitative approach with primary and secondary data types. Data collection techniques use interviews, observation and documentation which are then analyzed qualitatively with interactive models. The research findings are that eyebrow lamination can be applied to the makeup of hijab brides, modern brides and traditional Javanese brides. The application of eyebrow lamination in bridal make-up is very suitable for thick eyebrows with a rough hair character and a darker color because the resulting eyebrows are thicker, fuller, neater and longer lasting.